Website socialization as a marketing media for well drilling services in Kalisongo Village, Malang City - Hudriyah Mundzir; Shohib Muslim; Yushintia Pramitarini; Abdul Chalim; Mohammad Fahrial Amrulla (University of Merdeka Malang, 2022)
Various problems faced by well drillers in carrying out drilling. The problem is the lack of understanding of well drillers in marketing well drilling services that are in accordance with today's all-digital conditions. The next problem is the well drillers who do not understand and apply occupational health and safety when drilling. The purpose of this community service is to increase the productivity of artesian well drillers in Kalisongo Village, Dau District, Malang Regency, which is carried out by the method of socializing the website as a marketing medium for well drilling services and introducing website marketing of well drilling services to well drillers and understanding the importance of implementing health and work safety. The result of our dedication is the formation of the matair.id website as a marketing medium for artesian well drilling services and the application of occupational health and safety for well drillers.